Evaluasi Pengelolaan Obat dı Puskesmas Tampang Tumbang Anjir Kuala Kurun Kabupaten Gunung Mas Kalimantan Tengah Perıode Tahun 2022 - Wan Syurya Tri Dharma; Cinthia Cristiana (Journal Borneo, 2023)
Management and storage of drugs is a very important aspect. Therefore, the management and storage of drugs need to be carried out as well as possible to prevent drug damage. This writing aims to evaluate the drug administration information data at the Tampang Tumbang Anjir Health Center, Tampang Tumbang Anjir District, Gunung Mas Regency, Central Kalimantan. This study uses a non-experimental observational method which has a quantitative descriptive nature. The data in this study were taken concurrently from prescription sheets, stock cards, labeling, and waiting times for prescription services. This study obtained the results of the percentage value of damaged or expired goods (18.09%), 1-month availability (1.3 months), number of drug items per prescription (0.37%), the average speed of non-concoction prescription service (1.52 minutes), the average speed of concoction prescription service (1.01 minutes), and the percentage of drug labeling (0%). So it can be concluded that the management of drugs at the Tampang Tumbang Anjir Public Health Center, Gunung Mas Regency, Central Kalimantan is not good because there are still some that do not meet the applicable regulatory standards, namely the National Formulary (FORNAS) and DOEN.